2019
DOI: 10.1002/gps.5240
|View full text |Cite
|
Sign up to set email alerts
|

Perceived threat of Alzheimer's disease and related dementias in Chinese older adults: The role of knowledge and perceived stigma

Abstract: ObjectivesThis study focused on perceived threat of Alzheimer's disease and related dementias (ADRD) in Chinese older adults and investigated its associations with their perceived stigma and knowledge of ADRD.MethodsWe examined Chinese older adults' perceived threat of ADRD and its associations with perceived stigma, knowledge of ADRD, family variables and health variables. Data for this cross‐sectional study were collected by student interviewers in 2016. The participants (N = 754) were recruited from two urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
2
11
0
5
Order By: Relevance
“…With older people in China, the level of dementia knowledge reported in this study (58.3%) is similar to those reported by Zhang et al and Gao et al (55.5% and 61.3%,respectively), but higher than that reported in Huang's study (45.1%) (Gao et al, 2020;Huang et al, 2014;Zhang et al, 2017). In these studies, participants were all recruited from urban areas, and the dementia knowledge scales were standardized.…”
Section: Overall Dementia Knowledge Among Older Chinese Adults In Two Citiessupporting
confidence: 87%
See 1 more Smart Citation
“…With older people in China, the level of dementia knowledge reported in this study (58.3%) is similar to those reported by Zhang et al and Gao et al (55.5% and 61.3%,respectively), but higher than that reported in Huang's study (45.1%) (Gao et al, 2020;Huang et al, 2014;Zhang et al, 2017). In these studies, participants were all recruited from urban areas, and the dementia knowledge scales were standardized.…”
Section: Overall Dementia Knowledge Among Older Chinese Adults In Two Citiessupporting
confidence: 87%
“…To our knowledge, no studies have examined older Chinese adults living in China compared with their counterparts living overseas. In studies conducted in mainland China, Zhang et al and Gao et al reported the correct response rates of two standardized dementia knowledge scales as 55.5% and 61.3%, respectively, in urban-dwelling older adults (Gao et al, 2020;Zhang et al, 2017). In contrast, Zheng et al reported that only 28.8% of older Chinese Americans recognized dementia as a chronic mental illness (Zheng and Woo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Younger agers’ hesitation was in accordance with previous studies of stigma from dementia (Kahn et al., 2016). Moreover, a study with general people as the subjects suggested that people have a trend to perceive stigma of dementia in their “acquaintance community” (Gao et al., 2020). Relating to this study, our result in the SEM may show that wives, husbands, and siblings who knew neighbors of PWD more than other relatives, tended to hide the dementia of the PWD by being scared of “loss of face” (Woo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…29,29,37 También el componente emocional, en el que se describen emociones y sentimientos de la gente hacia la EA, mostró estar asociado con variables sociodemográficas como edad 29,31,40, género 29 , grupo étnico, nivel educativo 36,40 , estatus socioeconómico 29,32 y las experiencias previas con esta afección. 47 Predominan en la literatura disponible sobre este componente actitudinal, vergüenza, desconcierto, miedo a la exclusión 20,48 , tristeza 42,49,50 , ira 50 , aislamiento 42,49 , miedo 22,51,52 y percepción de amenaza. 51 El estudio de A Wang y col. realizado hace poco en Asia (China, India y Malasia), mostró que este miedo a la EA es mayor en las mujeres, en quienes viven en zona urbana y los que tienen empleo y son profesionales.…”
Section: Creenciaunclassified
“…47 Predominan en la literatura disponible sobre este componente actitudinal, vergüenza, desconcierto, miedo a la exclusión 20,48 , tristeza 42,49,50 , ira 50 , aislamiento 42,49 , miedo 22,51,52 y percepción de amenaza. 51 El estudio de A Wang y col. realizado hace poco en Asia (China, India y Malasia), mostró que este miedo a la EA es mayor en las mujeres, en quienes viven en zona urbana y los que tienen empleo y son profesionales. También se han reportado sentimientos de preocupación 22,51 por el estrés que el cuidado de alguien con EA puede causar a la familia, el impacto de la pérdida de memoria, la incertidumbre de desarrollar EA y un miedo mayor a sufrirlo frente a otras enfermedades51 y la aparición de algunos síntomas.…”
Section: Creenciaunclassified